Strategi Survival Pekerja Migran di Masa Pandemi Covid-19 di Suralaga, Lombok Timur - Saipul Hamdi; Syarifuddin Syarifuddin; Oryza Pneumatica Indrasari; Mutia Maesarah (Universitas Mataram, 2022)
The profession of immigrant workers is a very promising profession and is the main source of finance for workers and their families left behind. The money they get is usually used for various needs including building a house, financing children's education and also as business capital. However, with the emergence of the Covid-19 pandemic, this group of migrant workers is finding it difficult to maintain their businesses. This article aims to find out the economic challenges faced by migrant workers during the pandemic, and the strategies used by groups of migrant workers to survive amidst the threat of the Covid-19 economic crisis. This research was conducted for 6 months using qualitative research and analysis using phenomenology. Data collection techniques through observation-participation, FGD interviews, and documentation. This study took a sample of 25 people. The findings in the field show that the obstacles faced by migrant workers during the Covid-19 pandemic are in the form of termination of employment, wages that are not full, an increase in the price of goods, and also reduced money sent to families in Indonesia. As for the survival strategy carried out by groups of migrant workers during this pandemic, by doing farming, raising livestock and also utilizing the remaining savings from their results to become migrant workers. In addition, the government provides assistance such as BST assistance, MSME development and also provides training in the form of catfish or the so-called prinisan catfish cultivation program (Bule Baper). Apart from this strategy, there are also other strategies such as returning to being a migrant worker through legal and illegal channels.